An exhausted phenotype of TH2 cells is primed by allergen exposure, but not reinforced by allergen‐specific immunotherapy. Issue 9 (26th May 2021) - Wang, Shu‐Hung; Zissler, Ulrich M.; Buettner, Maren; Heine, Sonja; Heldner, Alexander; Kotz, Sebastian; Pechtold, Lisa; Kau, Josephine; Plaschke, Mirjam; Ullmann, Julia T.; Guerth, Ferdinand; Oelsner, Madlen; et al.
Abstract: Background: Studies show that proallergic TH 2 cells decrease after successful allergen‐specific immunotherapy (AIT). It is likely that iatrogenic administration of allergens drives these cells to exhaustion due to chronic T‐cell receptor stimulation. This study aimed to investigate the exhaustion of T cells in connection with allergen exposure during AIT in mice and two independent patient cohorts. Methods: OVA‐sensitized C57BL/6J mice were challenged and treated with OVA, and the development of exhaustion in local and systemic TH 2 cells was analyzed. In patients, the expression of exhaustion‐associated surface markers on TH 2 cells was evaluated using flow cytometry in a cross‐sectional grass pollen allergy cohort with and without AIT. The treatment effect was further studied in PBMC collected from a prospective long‐term AIT cohort. Results: The exhaustion‐associated surface markers CTLA‐4 and PD‐1 were significantly upregulated on TH 2 cells upon OVA aerosol exposure in OVA‐allergic compared to non‐allergic mice. CTLA‐4 and PD‐1 decreased after AIT, in particular on the surface of local lung TH 2 cells. Similarly, CTLA‐4 and PD‐1 expression was enhanced on TH 2 cells from patients with allergic rhinitis with an even stronger effect in those with concomitant asthma. Using an unbiased Louvain clustering analysis, we discovered a late‐differentiated TH 2 population expressing both markers that decreased during up‐dosing but persisted long term during the maintenance phase. Conclusions: This study shows that allergen exposure promotes CTLA‐4 and PD‐1 expression on TH 2 cells and that the dynamic change in frequencies of exhausted TH 2 cells exhibits a differential pattern during the up‐dosing versus the maintenance phases of AIT. Abstract : This study shows that TH 2 cells upregulate the exhaustion‐associated surface markers CTLA‐4 and PD‐1 upon in vivo allergen exposure in OVA‐sensitized mice and grass pollen‐allergic patients. This upregulation is reduced after AIT, in particular in TH 2 cells from local mouse lungs and AR patients with concurrent asthma. The transcriptome of allergic mouse lungs shows enhanced expression of both markers. Abbreviations: AAI, allergic airway inflammation; AIT, allergen‐specific immunotherapy; AR, allergic rhinitis; Baz1a, bromodomain adjacent to zinc finger domain 1A; CTLA‐4, cytotoxic T‐lymphocyte‐associated antigen‐4; Egr2, early growth response 2; Hif1a, hypoxia inducible factor 1 subunit alpha; Icos, inducible T cell costimulator; OVA, ovalbumin; PD‐1, program death protein‐1; Pdcd1, programmed cell death 1; Pilra, paired immunoglobin like type 2 receptor alpha; Tnfsf, TNF superfamily member; Tnfrsf, TNF receptor superfamily member; Tshz2, teashirt zinc finger homeobox 2